2011
DOI: 10.1016/j.socscimed.2010.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Job loss and depression: The role of subjective expectations

Abstract: Although the importance of expectations is well documented in the decision-making literature, a key shortcoming of the empirical research into effects of involuntary job loss on depression is perhaps its neglect of the subjective expectations of job loss. Using data from the US Health and Retirement Study surveys we examine whether the impact of job loss on mental health is influenced by an individual’s subjective expectations regarding future displacement. Our results imply that, among older workers in the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 31 publications
4
42
0
Order By: Relevance
“…Several studies have identified a link between recessions and mental health. For example, Mandal et al (2011) show that in addition to actual job loss, subjective expectations of future job loss are predictive of depression among older adults. McInerney et al (2013) find that the large wealth losses associated with the October 2008 stock market crash resulted in declines in subjective mental health measures.…”
Section: Tablementioning
confidence: 99%
“…Several studies have identified a link between recessions and mental health. For example, Mandal et al (2011) show that in addition to actual job loss, subjective expectations of future job loss are predictive of depression among older adults. McInerney et al (2013) find that the large wealth losses associated with the October 2008 stock market crash resulted in declines in subjective mental health measures.…”
Section: Tablementioning
confidence: 99%
“…A variety of psychiatric conditions including depression, anxiety, and borderline personality disorder have been associated with years-long trait-like reactions to loss of something valued including a loved one (Turvey et al, 1999), pregnancy (Gong et al, 2013), an attachment relationship including marriage (Distel et al, 2011; Stalker and Davies, 1995), a job (Mandal et al, 2011), a capability such as vision (Zhang et al, 2013) or hearing (McDonnall, 2009), resources (Luyster et al, 2006), hair (Schmitt et al, 2012), or an expected reward (Huston et al, 2013). Repetitive thinking about what was lost, and about associated negative feelings has been identified with the transformation of loss into profound and often very negative outcomes (Nolen-Hoeksema et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, layoffs and firing are likely to be endogenous (e.g., due to worker incompetence), and the use of these measures may have biased earlier findings (Charles and Stephens 2004; Dooley, Fielding, and Lennart 1996; Gibbons and Katz 1991; Hu and Tabor 2005; Weiss 1995). In contrast, business closings are more typically occasioned by external influences, such as an organizational decision to restructure or relocate business units (Brand, et al 2008; Mandal, et al in press). Note that one cannot conclusively state that business closures are exogenous events.…”
Section: Introductionmentioning
confidence: 99%